TEOLOGI MUSTADH’AFIN DALAM SURAT AN-NISA AYAT 97 DAN 98 PERSPEKTIF IMAM AL-ALŪSĪ : (STUDI KITAB TAFSIR RUH AL-MA’ANI) - Muhamad Hafizh; Agus Ali Dzawafi Agus Ali Dzawafi (Al-Fath, 2023)
This research analyzes the mustadh'afin theology in Surah an-Nisa verses 97 and 98 from the perspective of Imam al-Alūsī in his book Ruḥ al-Maʿānī, in outline explaining the command to the mustadh'afin to fight against various forms of oppression. Mustadh'afin are a group of people who are targeted for oppression because they have been weakened physically, intellectually, economically and in their thinking and have no enthusiasm for life. Using the Tafsir Ruḥ al-Maʿānī book in analyzing the meaning contained in the mustadh'afin verses, the aim of this research is to find the implied meaning, because the book Tafsir Ruḥ al-Maʿānī uses the Isyari or amali Sufism interpretation style. The method used in this research is library research with a descriptive analytical approach, using the book Tafsir Ruḥ al-Maʿānī as a primary source and secondary sources taken from scientific research on the mustadh'afin. Reviewing the mustadh'afin in general and based on Imam al-Alūsī's interpretation provides a structured understanding in this research, thereby keeping the discussion focused on one topic in finding reformers in the Islamic intellectual treasures. Keywords: Mustadh'afin, Book of Ruḥ al-Maʿānī, Thoughts of Imam al-Alūsī.